2009
DOI: 10.1152/ajpendo.90944.2008
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes induces and calcium channel blockers prevent cardiac expression of proapoptotic thioredoxin-interacting protein

Abstract: Chen J, Cha-Molstad H, Szabo A, Shalev A. Diabetes induces and calcium channel blockers prevent cardiac expression of proapoptotic thioredoxin-interacting protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
92
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 39 publications
6
92
0
1
Order By: Relevance
“…In this study, our results showed that TXNIP expression was significantly increased in the diabetic rat hearts, at both mRNA level and protein level. This is consistent with other reports in many types of cells including cardiomyocytes [39], and even in human diabetes [40]. High glucose has been identified as an important trigger of TXNIP upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, our results showed that TXNIP expression was significantly increased in the diabetic rat hearts, at both mRNA level and protein level. This is consistent with other reports in many types of cells including cardiomyocytes [39], and even in human diabetes [40]. High glucose has been identified as an important trigger of TXNIP upregulation.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study demonstrated that inhibiting TXNIP using calcium channel blockers can prevent cardiac apoptosis. 31 This is of importance as reduced Trx has also been shown to play a key role in regulating apoptosis pathway by binding to ASK-1 through redox active site of Trx. 32 Thus, inactivation of Trx through oxidation or interaction with TXNIP leads to release and activation of the apoptotic ASK-1.…”
Section: Figure 5 Fetpps Blocked Activation Of P38 Mapk Apoptosis Pamentioning
confidence: 99%
“…Throughout the process of apoptosis, proteins of the caspase and Bcl-2 families have crucial roles. Apoptosis is an important mechanism of myocardial cell damage in diabetic disease, and proteins of the caspase and Bcl-2 families are also involved (Li et al, 2008;Chen et al, 2009;Liu et al, 2009;Thandavarayan et al, 2009). CASP3 is a member of the caspase family and has been recognized as an important initiator and promoter of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac apoptosis as a major early cellular response in DM is induced by hyperglycemia-derived oxidative stress that activates a mitochondrial cytochrome c-mediated CASP3 pathway (Cai et al, 2006). Cleaved CASP3 has also been found to be elevated in vivo in STZ-and obesity-induced DM mice (Li et al, 2008;Chen et al, 2009). Down-regulation of CASP3 can prevent diabetes-and angiotensin II-induced cardiac endoplasmic reticular stress and associated cell death (Xu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%